2013
DOI: 10.1155/2013/438412
|View full text |Cite
|
Sign up to set email alerts
|

Inflammation in Retinal Vein Occlusion

Abstract: Retinal vein occlusion is a common, vision-threatening vascular disorder. The role of inflammation in the pathogenesis and clinical consequences of retinal vein occlusion is a topic of growing interest. It has long been recognized that systemic inflammatory disorders, such as autoimmune disease, are a significant risk factor for this condition. A number of more recent laboratory and clinical studies have begun to elucidate the role inflammation may play in the molecular pathways responsible for the vision-impa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
48
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(50 citation statements)
references
References 56 publications
0
48
0
2
Order By: Relevance
“…The exact pathogenesis is poorly understood, but various cardiovascular, thrombophilic, systemic, and ocular conditions predispose to CRVO [3] , while local inflammation has been also implicated in the pathophysiology of CRVO [4] . Additionally, several studies have identified a direct correlation between vascular endothelial growth factor (VEGF) levels and the severity of macular edema, as well as the development of retinal ischemia in CRVO, which are considered as the main causes of visual impairment in patients with CRVO [5][6][7] .…”
Section: Introductionmentioning
confidence: 99%
“…The exact pathogenesis is poorly understood, but various cardiovascular, thrombophilic, systemic, and ocular conditions predispose to CRVO [3] , while local inflammation has been also implicated in the pathophysiology of CRVO [4] . Additionally, several studies have identified a direct correlation between vascular endothelial growth factor (VEGF) levels and the severity of macular edema, as well as the development of retinal ischemia in CRVO, which are considered as the main causes of visual impairment in patients with CRVO [5][6][7] .…”
Section: Introductionmentioning
confidence: 99%
“…1,2 It is characterized by variable degrees of ischemia and edema, which frequently lead to vision loss and blindness if inadequately treated. [1][2][3] Uveitis is also a leading cause of visual impairment, 3 accounting for 30,000 new cases of legal blindness annually in the Western world. 4 Posterior uveitis affects the retina, choroid, and occasionally the optic nerve and comprises 10%-40% of all uveitis cases.…”
Section: Introductionmentioning
confidence: 99%
“…18 Recently, inflammatory processes have been implicated in vitreoretinal diseases, including RVO. 19,20 Several studies demonstrated elevated proinflammatory factors in the vitreous fluid of RVO patients and hypothesized that the inflammatory process is important in the development of RVO. 19,20 Inflammation within the ocular tissue has been implicated to play an important role in the development and pathogenesis of RVO.…”
mentioning
confidence: 99%